Assessment of the Effects Following Subchronic Dosing with Sodium Tungstate on Male Reproductive System in Wistar Rats - Nidhi Mathur, Geeta Pandey*, Prof Gyan Chand Jain, (Recent Research in Science and Technology, 2011)
Sodium tungstate is one of the inorganic compound with insulinomimmetic properties. The present study was conducted to investigate the effects of sodium tungstate on male reproductive system. The experimental rats were randomly divided into two groups (n=8/ group). The first group was used as a control, the second group was used to study the effect of sodium tungstate. Sodium tungstate was orally administrated to male Wistar rats at a dose level of 50mg/kg.bd wt. /day for 60 days. The daily administration produced no significant changes in the body weight gain. No significant changes were observed in the weight of testis, epididymis, seminal vesicles, ventral prostate, liver, kidney, and adrenal gland. Exogenous Ã‚Â supplementation with Sodium tungstate produce non significant depletion in protein, glycogen and sialic acid content in testis and epididymis and fructose level in seminal vesicle. Cholesterol level showedÃ‚Â no significant change in testis and epididymis. However, Spermatozoon motility and epididymal sperm concentration showed no significant changes. Plasma testosterone, FSH and LH level showed non significant decline in the sodium tungstate treated animals when compared to the control animals.The histology of testis and cauda epididymis showed no severe histological alterations when compared to control group. The results conclude that sodium tungstate (50 mg/kg bd.wt./day) did not cause any severe histological and biochemical alteration in male reproductive system.